Fractal analysis of daily market returns - Cheong, Yew Fai (2008)
It is the aim of the authors to show that a fractal analysis is comparable with, if not superior to, the traditional approaches. This report will adopt the methodology from a recent study (Kulish et al., 2006) analyzing human electroencephalograms as fractals and extend the analysis to the financial markets.